Design of Mobile Reservation for Go Kart Driving Application in UUM - Shrif, Mohamed Ali Salem (2009)
Mobile reservation has been popular worldwide. As it has become ubiquitous and customer can make a call from anytime to get transactions and the other facility of mobile phone is its mobility that makes it available anywhere. Mobile phone market shares have been dramatically make up, mobile commerce attracts variously companies, such as mobile handset manufacturers, mobile operators, financial institute, and several developers endeavouring, to develop technologies to generate added values for their mobile sphere. This study set out to identify requirements for Go Kart reservation system. The requirements identified has been documented and modelled in UML diagrammed, and validated with a prototype.